Tobacco use among Australian dental hygiene students is declining, but more still needs to be done - Hayes, Melanie J (BioMed Central, 2013)
While health care professionals have a responsibility to prevent and control the use of tobacco for improved health outcomes, it appears that some dental hygiene students continue to smoke. A survey of Australian dental hygiene students found that up to 16.3% smoke, although this prevalence rate decreased with each year of study. As future role models, it is essential that smoking cessation counselling is embedded in the dental curriculum to not only discourage their own habits, but so that they may promote the importance of being tobacco free to the wider population.